A kind of hexagonal boron nitride nanosheet and preparation method thereof

By combining the precursor method and the molten salt method, the problems of low yield, large energy consumption and low crystallinity in the existing boron nitride production process are solved, and high purity and high crystallinity hexagonal boron nitride nanosheets are prepared at a lower temperature, which is suitable for large-scale production.

CN116216661BActive Publication Date: 2025-04-25SHANGHAI UNIV

Patent Information

Application Number
CN202310157881.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-04-25
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

The existing boron nitride production process has problems such as low yield, large energy consumption, and difficulty in obtaining nano-size h-BN with high crystallinity.

Method used

The precursor method combined with the precursor method and the molten salt method are adopted to prepare the precursor by uniformly mixing the ball mill and then heated in a protective atmosphere, then mixed with the molten salt, calcined at high temperature, washed, suction filtered, and dried to obtain hexagonal boron nitride nanosheets.

Benefits of technology

Preparation of nanoscale hexagonal boron nitride at lower temperatures (1200°C) reduces energy consumption, improves the purity and crystallinity of the product, and is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116216661B_ABST
    Figure CN116216661B_ABST
Patent Text Reader

Abstract

The present invention relates to a hexagonal boron nitride nanosheet and a preparation method thereof, the preparation method comprising the following steps: S1, ball-milling a boron-containing compound and a nitrogen-containing compound, mixing them uniformly, heating them in a protective atmosphere, and preparing a precursor; S2, ball-milling the precursor obtained in step S1 and a molten salt, mixing them uniformly, calcining them at high temperature in a protective atmosphere, washing, filtering, and drying them after cooling to room temperature, and obtaining hexagonal boron nitride nanosheets. Compared with the prior art, the present invention can obtain nano-scale hexagonal boron nitride at a relatively low temperature of 1200°C, and the heating process has lower energy consumption and is more cost-saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of boron nitride preparation, in particular to a hexagonal boron nitride nanosheet and a preparation method thereof. Background Art

[0002] Hexagonal boron nitride (h-BN) is a non-oxide ceramic material with a graphite-like structure. Due to its excellent thermal conductivity, insulation, chemical stability and lubricity, it is widely used in casting, composite materials, cosmetics and other fields. With the development of microelectronics integration technology, electronic components are facing the problem of high heat generation. The application of h-BN as a thermal conductive filler in the field of composite materials is conducive to changing this situation. For example, when resin-based h-BN nanocomposites are used in semiconductor devices such as computer chips and 5G chips, the overall heat dissipation capacity of the device can be improved, and there is no effect on the surface circuit of the chip, which makes it promising to replace the commonly used silicon dioxide insulating protective layer. When preparing high thermal conductivity h-BN / polymer composites, compared with traditional micron-sized h-BN particles, h-BN nanosheets have a larger specific surface area, which can reduce the interfacial thermal resistance between it and the polymer matrix and improve the thermal conductivity of the material. In the field of optoelectronic applications, by implanting external factors on the surface of h-BN nanosheets, its electronic structure can also be changed to change the electronic and optical properties, which can be used to make deep ultraviolet emitters and various optoelectronic nanodevices.

[0003] At present, the preparation methods of h-BN powder mainly include the following:

[0004] 1. Traditional high temperature method

[0005] The traditional high-temperature method is an important method for preparing h-BN powder. The most commonly used method in industry is to use borax and urea (or ammonium chloride) as raw materials, mix them and prepare h-BN particles at high temperature in an ammonia or nitrogen atmosphere in a solid-phase reaction. The high-temperature method for preparing h-BN has a simple production process and is suitable for industrial production.

[0006] 2. Chemical vapor deposition

[0007] The chemical vapor deposition method for preparing h-BN nanosheets generally uses a hot wall reactor, where gaseous raw materials containing B and N are introduced into the reaction chamber through a carrier gas, and chemical reactions occur between the gaseous raw materials at high temperatures to generate h-BN particles. The hexagonal boron nitride nanoparticles prepared by the chemical vapor deposition method are of high purity and controllable shape, and various forms of BN can be generated by changing the reaction conditions and the type of substrate.

[0008] 3. Precursor method

[0009] This method is similar to the traditional high-temperature method, but the difference is that the precursor method does not directly calcine the raw materials at high temperature after mixing them, but prepares the raw materials at a lower temperature to generate a single, stable boron-nitrogen intermediate product, which is then calcined at high temperature to finally obtain hexagonal boron nitride powder. Compared with the traditional high-temperature method, this method retains the advantages of simple preparation method and suitability for large-scale production, while also having the characteristics of single phase and high purity of the prepared product.

[0010] At present, the more mature boron nitride production process is to prepare hexagonal boron nitride products by mixing boric acid and melamine for high-temperature reaction. This preparation method uses high-temperature heating and solid-phase reaction methods, but the existing production process has the following shortcomings: (1) Low yield: Due to the volatilization of gas during the solid-phase reaction, a large amount of reactants are lost, and the final product is very small; (2) High energy consumption: Since it is necessary to heat to 1800-1900℃ to obtain hexagonal boron nitride with good crystallinity, the entire process consumes a lot of energy and has high production costs. (3) It is difficult to obtain high-crystallinity nano-sized h-BN: Due to the high calcination temperature of the solid-phase reaction method, the product can only obtain micron-sized h-BN powder. If the temperature is lowered, the small-sized boron nitride particles obtained have low crystallinity. High-crystallinity h-BN nanosheets can be prepared by chemical vapor deposition, but there are problems such as high equipment requirements, uneven product shape and size, and inability to be mass-produced industrially. Similar to the traditional high-temperature method, the precursor method is still a solid-phase reaction with slow material transfer during the high-temperature calcination stage, so it is difficult to react completely. Therefore, developing a low-cost, high-purity preparation technology for h-BN nanosheets with uniform chemical composition is a research focus in the field of boron nitride production.

[0011] The molten salt method is a powder synthesis method in which the reactants of the required components are mixed with one or more salts in a certain proportion, and then calcined at a temperature higher than the melting point of the salt. Finally, the product is cooled and washed with deionized water to remove the salt therein to obtain a pure product. This method uses safe, non-toxic and recyclable molten salt as a medium to promote the diffusion of reactants and the reaction between them, and can synthesize nano-sized high-crystallinity powder particles at a lower temperature. In recent years, some researchers have used microwave molten salt method to prepare high-purity hexagonal boron nitride, but one of the raw materials used in this method is flammable magnesium powder, the preparation process has a high risk factor, and the microwave heating method is difficult to apply to large-scale production, and the practicality is not high. Some people also use raw materials similar to the present invention to prepare h-BN powder by molten salt method, but the obtained products are mostly micron-sized h-BN particles. At the same time, because the raw materials are directly mixed by nitrogen-containing compounds and boron-containing compounds, this method has the disadvantage of impure products due to uneven mixing.

[0012] Patent CN114836205A discloses a rare earth doped boron nitride nano powder and its preparation method. The technical scheme of the invention is: the molar ratio of boric acid to nitrogen-containing organic compound is 2:1, the ingredients are mixed, and then deionized water is added to the mixed mixture, and stirred to obtain solution A; the molar ratio of boric acid to rare earth nitric acid compound is 2: (0.01-0.05), rare earth nitrate compound is added to the solution A, stirred, and dried to obtain a composite precursor. Then 15-40wt% of the composite precursor is mixed with 60-85wt% of molten salt, and the temperature is raised to 1000-1200℃ at a rate of 4-6℃ / min under nitrogen or ammonia atmosphere, kept warm for 3-4h, and cooled naturally; washed, filtered, and dried to obtain rare earth doped boron nitride nano powder. In the method disclosed in the patent, the composite precursor is prepared in a solution by wet chemical method, which requires stirring, long-term drying and other processes. The process is complicated and the cycle is long, which is difficult to apply in actual production. In addition, there are many impurity peaks in the XRD spectrum of the obtained h-BN, indicating that there are impurities in the product. And the final product of h-BN is a rod-shaped structure, which is not conducive to heat dissipation. Summary of the invention

[0013] The purpose of the present invention is to provide a hexagonal boron nitride nanosheet and a preparation method thereof in order to overcome the defects of the above-mentioned prior art such as low yield, low purity, and unsafe raw materials. The preparation method combines a precursor method and a molten salt method.

[0014] The purpose of the present invention can be achieved by the following technical solutions:

[0015] One of the technical solutions of the present invention is to provide a method for preparing hexagonal boron nitride nanosheets, comprising the following steps:

[0016] S1. ball-milling a boron-containing compound and a nitrogen-containing compound, mixing them uniformly, and heating them in a protective atmosphere to prepare a precursor;

[0017] S2. The precursor obtained in step S1 and the molten salt are ball-milled and mixed evenly, calcined at high temperature in a protective atmosphere, and washed, filtered, and dried after cooling to room temperature to obtain hexagonal boron nitride nanosheets.

[0018] In step S1, the boron-containing compound is selected from any one or more of boric acid, borax, boric oxide or pentaborate, and the nitrogen-containing compound is selected from any one or more of melamine, melamine diamide or urea.

[0019] Furthermore, in step S1, the molar ratio of N and B atoms in the nitrogen-containing compound and the boron-containing compound is 1:1 to 6:1.

[0020] Furthermore, in step S1, the protective atmosphere is nitrogen, the heating temperature is 250-300° C., and the heating time is 4-8 hours.

[0021] Furthermore, in step S2, the molten salt is selected from any one or more of sodium chloride, potassium chloride, magnesium chloride, potassium carbonate or lithium carbonate.

[0022] Furthermore, in step S2, the mass ratio of the precursor to the molten salt is 1:1 to 1:4.

[0023] Furthermore, in step S2, the protective atmosphere is nitrogen, the gas flow rate is 0.3-0.8 L / min, the high-temperature calcination temperature is 1200-1500°C, the calcination time is 3-6h, and the heating rate is 5-10°C / min.

[0024] Furthermore, in step S2, the washing process is as follows: stirring for 20 minutes using a magnetic stirrer under a 90° C. water bath heating condition; and using a double-layer slow filter paper for filtration.

[0025] Furthermore, in step S2, the drying temperature is 120-180° C., and the drying temperature is 6 hours.

[0026] The second technical solution of the present invention is to provide a hexagonal boron nitride nanosheet based on the preparation method as described in one of the above technical solutions.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The preparation method provided by the present invention combines the advantages of the precursor method and the molten salt method to produce nano-scale hexagonal boron nitride at a relatively low temperature of 1200°C. The heating process consumes less energy than the traditional preparation method (which needs to be heated to 1800-1900°C), thus saving costs.

[0029] (2) Compared with the traditional solid-phase reaction, the preparation method provided by the present invention provides a liquid-phase reaction environment for the precursor at high temperature in the molten salt, which reduces the loss of raw materials with the gas and has a high conversion rate of the product. At the same time, the liquid-phase environment makes the material transfer in the reactants faster, so that the h-BN crystals develop better and have higher crystallinity. In addition, the molten salt can be recycled to achieve the effect of green and recycling, saving costs.

[0030] (3) In the preparation method provided by the present invention, impurities are completely removed by washing and filtering, and the obtained hexagonal boron nitride has high purity.

[0031] (4) The product obtained by traditional solid phase reaction has a high degree of agglomeration, which is not conducive to the practical application of the powder, and the powder is often dispersed by mechanical ball milling or other methods. The hexagonal boron nitride powder prepared by the present invention has a low degree of agglomeration and the particles are easy to disperse.

[0032] (5) By changing the type of molten salt and calcination conditions of the present invention, hexagonal boron nitride particles of different sizes can be prepared to meet product requirements under different usage conditions.

[0033] (6) The preparation method provided by the present invention is entirely carried out through solid-phase reaction heating. It only requires the raw materials to be evenly mixed and then directly heated for a short time to obtain the precursor. The preparation method is simple and easy to apply to large-scale production. The h-BN product finally obtained is free of impurities and has a higher purity. The h-BN product is a lamellar nanoparticle, which is more conducive to the application in heat dissipation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the X-ray diffraction pattern of the hexagonal boron nitride prepared in Examples 1 to 3.

[0035] Figure 2 This is a scanning electron microscope photograph of the hexagonal boron nitride prepared in Example 1.

[0036] Figure 3 This is a scanning electron microscope photograph of the hexagonal boron nitride prepared in Example 2.

[0037] Figure 4 This is a scanning electron microscope photograph of the hexagonal boron nitride prepared in Example 3.

[0038] Figure 5 This is the X-ray diffraction pattern of the hexagonal boron nitride prepared in Comparative Example 1.

[0039] Figure 6 This is a scanning electron microscope photograph of the hexagonal boron nitride prepared in Comparative Example 1. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0042] Embodiment 1:

[0043] Preparation of precursor: Boric acid and melamine were uniformly mixed by ball milling in a molar ratio of 2:1 and placed in an oven and heated under nitrogen to prepare a precursor at 280°C for 6 hours.

[0044] Mix 6g of the precursor with 12g of potassium chloride to obtain a uniform mixed powder; introduce the mixed powder into a graphite crucible and calcine it in a tubular furnace. The calcination conditions are: heat to 1200℃ at a rate of 5℃ / min for 3h under a nitrogen flow rate of 0.5L / min, and then cool to room temperature with the furnace. Stir and wash the prepared powder with deionized water and a magnetic stirrer in a 90℃ water bath for 20min, then filter it with a Buchner funnel lined with a double layer of slow filter paper, and repeat the entire washing and filtration process three times. Finally, use an oven to dry the powder at 180℃ for 6h to obtain h-BN. The product was analyzed by X-ray diffractometer, as shown Figure 1 The morphology was observed by scanning electron microscopy. Figure 2 shown.

[0045] Embodiment 2:

[0046] Preparation of precursor: Boric acid and melamine were uniformly mixed by ball milling in a molar ratio of 2:1 and placed in an oven and heated under nitrogen to prepare a precursor at 280°C for 6 hours.

[0047] Mix 6g of the precursor with 5.28g of sodium chloride and 6.72g of potassium chloride to obtain a uniform mixed powder; introduce the mixed powder into a graphite crucible and calcine it in a tubular furnace. The calcination conditions are: heat to 1200℃ at a rate of 5℃ / min for 3h under a nitrogen flow rate of 0.5L / min, and then cool to room temperature with the furnace. Stir and wash the prepared powder with deionized water and a magnetic stirrer in a 90℃ water bath for 20min, then filter it with a Buchner funnel lined with a double layer of slow filter paper, and repeat the entire washing and filtration process three times. Finally, use a drying oven to dry the powder at 180℃ for 6h to obtain h-BN. The product was analyzed by X-ray diffractometer, as shown Figure 1 The morphology was observed by scanning electron microscopy. Figure 3 shown.

[0048] Embodiment 3:

[0049] Preparation of precursor: Boric acid and melamine were uniformly mixed by ball milling in a molar ratio of 2:1 and placed in an oven and heated under nitrogen to prepare a precursor at 280°C for 6 hours.

[0050] Mix 6g of the precursor with 12g of potassium chloride to obtain a uniform mixed powder; introduce the mixed powder into a graphite crucible and calcine it in a tubular furnace. The calcination conditions are: heat to 1300℃ at a rate of 5℃ / min for 4h under a nitrogen flow rate of 0.5L / min, and then cool to room temperature with the furnace. Stir and wash the prepared powder with deionized water and a magnetic stirrer in a 90℃ water bath for 20min, then filter it with a Buchner funnel lined with a double layer of slow filter paper. Repeat the entire washing and filtration process three times. Finally, use a drying oven to dry the powder at 180℃ for 6h to obtain h-BN. Use an X-ray diffractometer to perform phase analysis on the product. Figure 1 The morphology was observed by scanning electron microscopy. Figure 4 shown.

[0051] Comparative Example 1:

[0052] Compared with Example 1, most of the above are the same except that the addition of molten salt is omitted. The product is analyzed by X-ray diffractometer. Figure 5 The morphology was observed by scanning electron microscopy. Figure 6 shown.

[0053] The test results are as follows:

[0054] like Figure 1 As shown, the XRD patterns corresponding to the hexagonal boron nitride prepared in Examples 1 to 3 all show sharp (002), (100), (101), (004), (110), and (112) h-BN characteristic peaks without impurity peaks, indicating that the h-BN prepared by the preparation method of the present invention is of high purity. By using a low-melting-point composite molten salt (Example 2) and increasing the calcination temperature and extending the calcination time (Example 3), the obtained h-BN diffraction peaks are sharper and have higher peak intensity, indicating that the crystal development is better. Figure 5 As shown, some h-BN characteristic peaks with large half-width appeared in the XRD spectrum of the product prepared in Comparative Example 1, indicating that the obtained BN crystal form is poorly developed and has low crystallinity.

[0055] Figure 2 , Figure 3 , Figure 4The SEM photos of h-BN prepared in Examples 1, 2, and 3 respectively show that the h-BN particles are well dispersed, but the particle morphology and size are different. Table 1 is the average particle size of h-BN particles obtained by statistics using Image Pro Plus software. It can be found that Example 1 obtained granular h-BN with an average size of 170nm under low temperature conditions of 1200°C. In Example 2, under the condition that other parameters remain unchanged and only the molten salt is changed to a composite molten salt of sodium chloride and potassium chloride, h-BN particles with an average size of 73nm are obtained. Compared with Example 1, the calcination temperature of Example 3 is increased to 1300°C and the calcination time is extended to 4h, and h-BN with a size of 214nm is obtained. Figure 6 This is a SEM photo of the product prepared in Comparative Example 1. It can be seen that the product exists in the form of large-sized agglomerates without obvious particles. Compared with Example 1, when other conditions are the same, the agglomerate product with poor crystal development is obtained without the addition of molten salt, and hexagonal boron nitride nanosheets with high crystallinity cannot be obtained.

[0056] Table 1 Average particle size of h-BN particles prepared in Examples 1 to 3

[0057]

[0058] The preparation of hexagonal boron nitride in industrial production faces the problems of high energy consumption, low product purity, low crystallinity, etc. The preparation method of the present invention can prepare hexagonal boron nitride nanosheets with high purity and good crystal development at a lower temperature, providing a certain technical reference for solving the above problems. And by changing the experimental parameters, such as the type of molten salt, calcination time and calcination temperature, the shape and size of the prepared h-BN particles can be regulated according to needs.

[0059] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing hexagonal boron nitride nanosheets, characterized in that: The steps include: Preparation of precursor: Boric acid and melamine were uniformly mixed by ball milling at a molar ratio of 2:1 and then placed in an oven and heated under nitrogen at 280 °C for 6 h to prepare the precursor; 6 g of the precursor was mixed with 5.28 g of sodium chloride and 6.72 g of potassium chloride to obtain a uniform mixed powder; the mixed powder was introduced into a graphite crucible and calcined in a tubular furnace under the following calcination conditions: heated to 1200 °C at a rate of 5 °C / min for 3 h under a nitrogen flow rate of 0.5 L / min, and then cooled to room temperature with the furnace; the prepared powder was stirred and washed with deionized water and a magnetic stirrer in a 90 °C water bath for 20 min, and then filtered with a Buchner funnel covered with a double-layer slow filter paper, and the entire washing and filtration process was repeated three times; finally, the powder was dried in a drying oven at 180 °C for 6 h to obtain hexagonal boron nitride nanosheets.

Citation Information

Patent Citations

  • Rare earth doped boron nitride nano-powder and preparation method thereof

    CN114836205A

Cited By

  • Boron nitride fiber-based ceramic material as well as preparation method and application thereof

    CN120736912A